1999
DOI: 10.1242/jeb.202.17.2281
|View full text |Cite
|
Sign up to set email alerts
|

The mechanics of sound production in the puff adder Bitis arietans (Serpentes: viperidae) and the information content of the snake hiss

Abstract: Puff adders (Bitis arietans), like many other snakes, hiss as part of their defensive repertoire. In B. arietans, the hisses have a clear quadraphasic pattern consisting of an initial exhalatory hiss, a brief transitional pause, an inhalatory hiss and a rest or breath-holding phase. Simultaneous recordings of body diameter, electrical activity in the intrinsic laryngeal musculature, airflow through the nasal passageway and sound production revealed that the anterior respiratory tract plays a passive role in hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…There is a lack of hearing research on Chinese striped-neck turtles; thus, further studies are needed to determine whether the turtles can hear their own high-frequency signals, or if it is just a potential functional signal redundancy as observed for some of the vocalizations of Alligator sinensis ( Todd, 2007 ; Wang et al, 2007 ; Wang et al, 2009 ). Snakes can produce sounds up to 10 kHz, which is well above their hearing range; however, the low level of acoustic specialization within the sounds produced by snakes and the low potential for encoded information content indicate limited communication capabilities ( Young et al, 1999 ; Young, 2003 ). It was reported that Ptyas mucosus may be an acoustic Batesian mimic of the king cobra, Ophiophagus hannah ( Young, Solomon & Abishahin, 1999 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is a lack of hearing research on Chinese striped-neck turtles; thus, further studies are needed to determine whether the turtles can hear their own high-frequency signals, or if it is just a potential functional signal redundancy as observed for some of the vocalizations of Alligator sinensis ( Todd, 2007 ; Wang et al, 2007 ; Wang et al, 2009 ). Snakes can produce sounds up to 10 kHz, which is well above their hearing range; however, the low level of acoustic specialization within the sounds produced by snakes and the low potential for encoded information content indicate limited communication capabilities ( Young et al, 1999 ; Young, 2003 ). It was reported that Ptyas mucosus may be an acoustic Batesian mimic of the king cobra, Ophiophagus hannah ( Young, Solomon & Abishahin, 1999 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pristidactylus valeriae hissed under predation risk, but some sound characteristics were treatment and sex-dependent since; for example, hisses emitted under threat were longer than those emitted under capture. Even if hisses only involve normal respiratory movements [52], prolonged and forced movements might require extra energy. In this context, emitting longer hisses when there is more probability to survive, threat vs. capture, may provide honest information on endurance to fight or escape, e.g., [53] and thus increase the chances to deter the predator.…”
Section: Discussionmentioning
confidence: 99%
“…Hisses are sounds with a simple structure and, at least for snakes, data show that they have high similarities across species [52]. In light of this, and considering that vocalizations uttered under predation risk tend to be conservative across taxa, e.g., [62,63], it can be hypothesized that hisses of Pristidactylus species may be similar across taxa.…”
Section: Discussionmentioning
confidence: 99%